Resources Management for School Effectiveness in the Era of Covid-19 Pandemic - ANYANWU, Oluwakemi Mogelola (International Journal of Educational Management, 2021)
The widespread of COVID-19 pandemic have been a huge challenge to education systems all across the globe. This perspective offers guidance to teachers, institutional heads, and officials on addressing the crisis and continuing effective of teaching and learning process. Fragment of the essential pre-requisites needed to be put in place in the school system for the actualization of the educational aim and purposes entails sufficient endowment of resources, supreme utilization and appropriate management of education resources to avoid wastages and improve the quality of the teaching - learning process the pandemic era. In ramping up capacity to teach during this period, schools and colleges management have to upgrade their educational resource in other to deliver effective teaching and learning, such as taking advantage of asynchronous learning, which works best in digital formats. The study used descriptive research method to gather information from one hundred teachers in secondary schools in Ado Ekiti with the use of structure questionnaire. The result of the findings revealed that materials/ physical resources, financial resources, time resources, human resources and communication technology resources are the major resources that affect secondary school effectiveness during COVID-19 crises and majority of the schools had to stop teaching and learning because they are not well equipped with ICT facilities. The result further showed that there is significant relationship between resources management and secondary schools’ effectiveness during COVID-19 pandemic in Nigeria in which the improvement in resources management level will also improve schooling effectiveness during crisis. This paper therefore suggested that government should provide relief funds to equip and resource schools for improved teaching and learning methods for effective teaching and learning during pandemic.